London and its Asylums, 1888-1914 - Ellis, Robert. author. aut Link
XV, 296 p. 13 illus., 6 illus. in color.
Keywords: 'This is an important and timely contribution to the politics of mental health. Ellis’s forensic dissection of the politics and finance of asylums in late nineteenth- and early twentieth-century London demonstrates the evolution of asylum and mental health care but also provides a nuanced account of local government and welfare activism in this period. This book is highly recommended for those interested not only in the history of mental health care, but also the sometimes internecine conflicts which underpinned urban government in the Victorian and Edwardian eras.' –Professor Heather Shore, Director of MCPHH, Department of History, Politics and Philosophy, Manchester Metropolitan University, UK This book explores the impact that politics had on the management of mental health care at the turn of the nineteenth and twentieth centuries. 1888 and the introduction of the Local Government Act marked a turning point in which democratically elected bodies became responsible for the management of madness for the first time. With its focus on London in the period leading up to the First World War, it offers a new way to look at institutions and to consider their connections to wider issues that were facing the capital and the nation. The chapters that follow place London at the heart of international networks and debates relating to finance, welfare, architecture, scientific and medical initiatives, and the developing responses to immigrant populations. Overall, it shines a light on the relationships between mental health policies and other ideological priorities.